Relação entre disponibilidade de água e aspectos vegetativos e reprodutivos de herbácea da caatinga - AGUIAR, Bruno Ayron de Souza (2017)
In semi-arid environments the development and survival of the plants are mainly controlled by the temporal and spatial heterogeneity of the pluviometric regime. In these environments, the prolonged effect of water scarcity can be determinant to adversely affect the phenological rhythm, limit plant growth and cause decline in reproductive processes. Thus, in order to understand the possible changes in the functioning of forests in semi-arid environments, this paper hypothesizes that reductions in vegetative and reproductive growth and delays in the phenological rhythm occur as water availability is reduced, using the geophysic Talinum paniculatum as a model To evaluate the effect of water deficiency on plant growth responses. Specifically, we try to answer the following questions in this study: (i) what happens to vegetative and reproductive growth of the plant by reducing 50% and 75% of water availability? (Ii) How much of the quantitative variations in the production of vegetative / reproductive structures and phenology can be explained by the reduction of water availability? (Iii) does the phenological rhythm of plants reflect the reduction of water availability? The water deficiency experiment was conducted during six months in a greenhouse using 150 individuals from the seedling stage, transplanted after ten days of germination until complete maturation, distributed equally in the treatments in different pot capacity (cp): T1 : 100% (cp-control), T2: 50% (cp) and T3: 25% (cp). Thirty plants (per treatment) were selected to quantify weekly vegetative growth and daily flower, fruit and seed production, as well as to monitor phenological behavior. Another 20 plants (per treatment) for morphometric measurements of flowers and fruits. The differences between the treatments and the explanatory power of the water reductions were evaluated by GLM analysis, incorporating ANOVA, with Tukey a posteriori test. The vegetative attributes of T. paniculatum differed significantly between treatments, but the diameter and accumulated leaves production did not show differences between T1 and T2, but differed from T3. There were significant differences in the production of flowers, fruit and seeds and in all morphometric measurements of flowers and fruits. The phenological rhythm of leaf senescence and foliar abscission did not differ significantly between treatments, but the budding in T3 differed from the others, with a gradual cessation of activity from week 17. The phenological rhythm of flowering, fruiting and dehiscence of fruits differed between treatments, with no flowering for T3 and delayed T2 production. The explanatory power of water presented a wide range of variation, from 21 to 71% for vegetative growth, from 41 to 97% for reproductive growth and from 5 to 61% for phenological rhythm. Reductions in water availability negatively influenced the phenology, vegetative and reproductive growth of T. paniculatum, with the most drastic quantitative reductions in the treatment that simulated higher water deficit. Thus, data from this study indicate that the consequences of reduced water availability on forest soil can lead to significant damage to herbaceous cover, reducing seed production annually to replenish forest soil stock.